Structural and electrochemical properties of LiNi0.7Co0.15Mn0.15O2 thin film prepared by high frequency hybrid direct current and radio frequency magnetron sputtering - Chung, Youngmin; Park, Ho-young; Oh, Si-hyoung; Yoon, Dong Young; Jin, Sang-wan; Jang, Dong-yoon; Ko, Jang Myoun; Cho, Won Il; Lee, Seong-Rae (SPRINGER, 2013)
A LiNi0.7Co0.15Mn0.15O2 thin film cathode has been successfully prepared by hybrid direct current - radio frequency magnetron sputtering onto glass substrate from the LiNi0.7Co0.15Mn0.15O2 target and post-annealed by the rapid thermal annealing process. Its structure and morphology were characterized by X-ray diffraction, and scanning electron microscopy while its chemical compositions were confirmed with the inductively coupled plasma atomic absorption spectrophotometer, Raman spectroscopy, Auger electron spectroscopy, and glow discharge spectrometer. Its electrochemical properties were measured by galvanostatic charge - discharge test and cyclic voltammetry. First discharge capacity of 73 mu Ah cm(-2) mu m(-1) was obtained from a half cell with the LiNi0.7Co0.15Mn0.15O2 thin film cathode and lithium metal anode in the potential range of 4.3 similar to 2.5 V at 30 mu A and its coulombic efficiency was more than 99 %.
Keywords: CHEMICAL-VAPOR-DEPOSITION; LITHIUM-ION BATTERIES; RECHARGEABLE MICROBATTERIES; CATHODES; LICOO2; PERFORMANCE; ELECTRODES